Preparation technology of deuterium isotope content standard sample in zirconium oxide layer

By depositing TiN/ZrO2-X/TiN composite coating on the zirconium alloy matrix and controlling the energy combination of deuterium isotope ion beams, the problem of uneven deuterium isotope content in the zirconium alloy samples was solved, and the precise control of deuterium isotope content in the zirconium alloy oxide layer was achieved and the preparation of standard samples was improved, which improved the accuracy and reliability of the determination.

CN119756981APending Publication Date: 2025-04-04SICHUAN UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411888011.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

It is difficult to accurately obtain zirconium alloy samples with different hydrogen (or deuterium) contents in the prior art, especially at the end of the design life of the heavy water reactor Zr-Nb2.5 alloy pressure tube, the deuterium isotope content is high and the traditional hydrogen permeation method has the problem of uneven distribution.

Method used

The TiN/ZrO2-X/TiN composite coating was deposited on the surface of single crystal silicon or Zr-Nb2.5 alloy matrix by vapor deposition technology, and the ZrO2-X layer was crystallized by high-temperature vacuum annealing. Then, the energy combination of the multi-beam hydrogen isotope ion beam is determined by using a computational simulation method to regulate the content of deuterium isotopes in the oxide layer of zirconium alloy to ensure its normal distribution or uniform distribution.

Benefits of technology

Accurate control of the deuterium isotope content in the zirconium alloy oxide layer, and standard samples are provided for correction and comparison of test results of advanced spectroscopy and mass spectrometry, improving the accuracy and reliability of the determination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119756981A_ABST
    Figure CN119756981A_ABST
Patent Text Reader

Abstract

The invention aims to disclose a preparation technology of a standard sample for calibrating deuterium-containing isotope components in a fuel cladding zirconium alloy oxide layer, which comprises the following steps: sequentially preparing a TiN / ZrO2-X / TiN coating on the surface of a monocrystalline silicon (Si) or Zr-Nb2.5 alloy matrix by adopting a vapor deposition technology, and then performing high-temperature vacuum annealing to obtain ZrO2-X (xlt; and finally, determining the energy combination of a plurality of hydrogen isotope ion beams, effectively regulating and controlling the content distribution of hydrogen isotopes in the zirconium alloy oxide layer, and finally obtaining the standard sample with the determined hydrogen (deuterium) isotope content in the ZrO2-X oxide layer. And a new technical approach is provided for correcting and comparing the accuracy and reliability of test results of spectrum and mass spectrometry. The deuterium isotope standard sample in the ZrO2-X layer in the TiN / ZrO2-X / TiN composite coating can be used for one-time spectrometric method calibration and can also be used for calibration of spectrum and mass spectrometry results of multiple measurement results, and the deuterium isotope standard sample in the ZrO2-X layer in the TiN / ZrO2-X / TiN composite coating is stable in structure and reliable in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention discloses a standard sample preparation technology for calibrating the deuterium isotope composition in the zirconium alloy oxide layer of the fuel cladding. The present invention adopts the vapor deposition technology to sequentially deposit single crystal silicon (Si) or Zr-Nb 2.5 The surface of the alloy substrate is first prepared with TiN / ZrO 2-X / TiN coating, and then high temperature vacuum annealing to obtain ZrO 2-X(x<0.05) Finally, the energy combination of multiple hydrogen isotope ion beams was determined based on the computational simulation method, effectively regulating the normal distribution or uniform distribution of hydrogen isotope content in the zirconium alloy oxide layer, and finally obtaining ZrO 2-X Standard sample for determining the hydrogen (deuterium) isotope content in the oxide layer. Background Art

[0002] Nuclear energy has potential advantages in solving energy problems due to its clean, economical and reliable characteristics. Zirconium alloys have been successfully used in reactors due to their low neutron absorption cross section, good radiation resistance and corrosion resistance. Among them, the unique structural characteristics of heavy water reactors give them the advantages of continuous refueling, the use of natural uranium fuel, and can also be used for radioactive isotopes. 60 Co production, along with pressurized water reactors and boiling water reactors, are the world's three major commercial water-cooled nuclear reactor types. The only heavy water reactor nuclear power plant currently in operation in my country is a turnkey project in Canada. 60 Co radioactive sources can meet 85% of the domestic market demand, creating good economic and social benefits. During the operation of the reactor, the zirconium alloy cladding tube will react with the cooling medium for corrosion. Part of the hydrogen (or deuterium) produced by the corrosion of the material will turn into hydrogen and enter the cooling medium, and the other part will be absorbed by the zirconium cladding. When the hydrogen (or deuterium) absorbed by the zirconium cladding exceeds its solid solubility limit, the excess hydrogen (or deuterium) will precipitate in its matrix in the form of hydrogen (or deuterium) compounds. Hydrogen (or deuterium) compounds are a brittle phase, and their presence will reduce the toughness of the zirconium alloy and seriously affect the safe and stable operation of the reactor. Zr-Nb 2.5The alloy pressure tube is the most important pressure-bearing boundary of the core of a heavy water reactor. Its special structural design and ultra-long design life place extremely high demands on material performance. During the operation of the reactor, the corrosion of heavy water as a coolant will not only cause the pressure tube to thin, but also increase the content of hydrogen isotopes deuterium in the zirconium alloy, increasing the risk of alloy embrittlement. The design life of the pressure tube is up to 30 years, which is about 30 times that of a typical cladding zirconium alloy (12-18 months), but its hydrogen isotope hydrogen (deuterium) content requirement at the end of its life is comparable to that of other zirconium alloy claddings. In recent years, research on the effect of hydrogen (or deuterium) on zirconium alloys has gradually received attention, so there is an urgent need to conduct in-depth and comprehensive research on the effect of different hydrogen contents on the mechanical properties of zirconium claddings. In this context, how to accurately obtain zirconium alloy samples with different hydrogen (or deuterium) contents has become the primary task for subsequent performance evaluation and risk assessment.

[0003] In order to obtain zirconium alloys with different hydrogen contents, the correct hydrogenation method must be selected first, and then a reasonable detection method must be selected to evaluate the hydrogen content. At present, the main methods for hydrogenation of zirconium alloys are electrolytic hydrogenation and gaseous hydrogenation. The hydrogenation temperature of the electrolytic hydrogenation method is low (60 ° C), and the hydrogenation time is long, generally requiring 8-24 hours. The diffusion rate of hydrogen atoms is slow at low temperatures, and it is easy to form a layer of hydride on the surface of the sample, thereby affecting the uniform distribution of hydrogen content. In contrast, the gaseous hydrogenation method has the characteristics of high hydrogenation temperature (450 ° C), fast hydrogenation rate (10 min), and uniform distribution of hydrogen content. It has been widely used in hydrogenation treatment of zirconium alloys. However, for heavy water reactors, the design life of the pressure tube is as long as 30 years, which is about 30 times that of typical cladding zirconium alloys (12-18 months), but its H content requirement at the end of its life is comparable to that of other zirconium alloy claddings. Therefore, the pressure tube is made of Zr-Nb 2.5 The alloy is manufactured using a number of processes to ensure that its corrosion resistance and hydrogen absorption resistance meet the design requirements. Pre-oxidation film treatment on the surface of zirconium alloy is one of the many surface modification methods. According to limited information, the pre-film treatment of the pressure pipe is to perform stress relief treatment in water vapor while forming a protective bright black pre-film on the surface. 2.5 The main component of the pre-film on the alloy surface is dense monoclinic zirconium oxide (ZrO 2-X ) and a small amount of tetragonal zirconia phase (ZrO 2 ). Due to Zr-Nb 2.5 The presence of pre-grown zirconium oxide film on the alloy surface was studied and evaluated by gas phase hydrogenation (or deuteration) method for Zr-Nb heavy water reactor. 2.5 Methods for studying hydrogen isotope distribution and diffusion behavior in alloys are also very limited.

[0004] At present, the commonly used methods for detecting hydrogen content are weighing method, metallographic method, chemical analysis method, spectroscopy (laser Raman spectroscopy, laser induced breakdown spectroscopy, Fourier transform infrared spectroscopy), gas chromatography and mass spectrometry (spark source mass spectrometry, secondary ion mass spectrometry, thermal vacuum extraction-quadrupole mass spectrometry). Among them, the metallographic method evaluates the hydrogen content in zirconium alloy by observing the number of hydrides after hydrogen permeation. This method is more intuitive, and the measured hydrogen content is related to the mechanical properties, but the test results have large errors or low confidence, and cannot be accurately quantified; the weighing method uses the increase in the mass of the sample after hydrogen absorption to calculate its hydrogen content. When the metallographic method is used to calculate the hydrogen content, it is affected by the mass of the sample itself and the accuracy of the analytical balance. Its accuracy is insufficient and the error is large, but this method can reflect the overall hydrogen content of the sample and is easy to operate; the commonly used chemical analysis method is the inert gas melting infrared absorption method, the principle of which is to melt the sample at high temperature to precipitate its hydrogen atoms and react with copper oxide to generate H 2 O. At a wavelength of 7.0 μm, H 2 The relationship between the absorption of infrared radiation by O and its concentration follows the Lambert-Beer law. A photoelectric detector can be used to detect the change in the light intensity of the infrared absorption cell, thereby converting its hydrogen content. This method has high detection accuracy, but is limited by the sampling location and has great limitations. It can only reflect the hydrogen content at a certain point, not the hydrogen content of the entire sample, and in the case of uneven hydrogen content, especially when hydride is precipitated, the test results have great volatility; Spectroscopy and mass spectrometry (such as secondary ion mass spectrometry, thermal vacuum extraction-quadrupole mass spectrometry) have high precision and accuracy, especially secondary ion mass spectrometry can detect the hydrogen isotope content of the sample along the thickness and depth direction, and the analysis and testing methods are relatively reliable and standard. However, the accuracy and reliability of the test results of spectroscopy and mass spectrometry (especially secondary ion mass spectrometry) lack the calibration and comparison of hydrogen isotope standard samples recognized by the industry.

[0005] The purpose of the present invention is to disclose a standard sample preparation technology for calibrating the deuterium isotope composition in the zirconium alloy oxide layer of the fuel cladding. The present invention adopts a vapor deposition technology to sequentially deposit single crystal silicon (Si) or Zr-Nb 2.5 The surface of the alloy substrate is first prepared with TiN / ZrO 2-X / TiN coating, and then high temperature vacuum annealing to obtain ZrO 2-X(x<0.05) Finally, the energy combination of multiple hydrogen isotope ion beams was determined based on the computational simulation method, effectively regulating the normal distribution or uniform distribution of hydrogen isotope content in the zirconium alloy oxide layer, and finally obtaining ZrO 2-X Standard sample for determining the isotope content of hydrogen (deuterium) in the oxide layer. It provides a new technical approach for calibrating and comparing the accuracy and reliability of test results of advanced spectroscopy and mass spectrometry (especially secondary ion mass spectrometry). Summary of the invention

[0006] The technical solution provided by the present invention is: a preparation technology of a standard sample of deuterium isotope content in a zirconium oxide layer, characterized in that the standard sample of deuterium isotope content in the zirconium oxide layer contains a specific phase structure ZrO 2-X(x<0.05) Contains a coating with a known isotopic deuterium content and a TiN deuterium diffusion barrier coating, TiN / ZrO 2-X / TiN is deposited on single crystal silicon (Si) or Zr-Nb 2.5 The surface of the alloy substrate, wherein: the ZrO 2-X(x<0.05) In the coating, the value of x is <0.05; in the TiN deuterium diffusion barrier coating, the atomic ratio of Ti:N is close to the equiatomic ratio, and the TiN / ZrO 2-X The preparation of the TiN / TiN composite coating is characterized by comprising the following steps: a. Cleaning substrate material: For single crystal Si substrate (or Zr-Nb 2.5 The alloy substrate is ground and polished), then degreased and cleaned, and after drying, placed in the vacuum chamber of the magnetron sputtering instrument, and the vacuum system is used to make the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa; b. Treatment of substrate before deposition: Keep the vacuum degree in the vacuum chamber less than 4.0×10 -4 Under the condition of 2.5-6 Pa, the single crystal Si or zirconium alloy substrate is back-sputtered and cleaned, the back-sputtering bias voltage is -1000~-700V; the back-sputtering gas is argon; the back-sputtering pressure in the vacuum chamber is 2.5-6 Pa, and the back-sputtering cleaning takes 8-12 minutes; c. Pre-sputtering: Keep the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa conditions, the target was cleaned by pre-sputtering for 15 min, where: the pre-sputtering power of the Ti target was 150-200 W; the pre-sputtering bias was -50~-100 V; the pre-sputtering power of the FeCrAlZr target was 150~200 W; the pre-sputtering bias was -50~ -100 V; the pre-sputtering gas was argon; the pre-sputtering gas pressure in the vacuum chamber was 0.37-0.4 Pa; d. Sputtering deposition of TiN / ZrO 2-X / TiN composite coating: Argon and nitrogen are introduced into the vacuum chamber at the same time, and a TiN layer is first deposited on a single crystal Si or zirconium alloy substrate. During the deposition process, the argon flow rate is 15-30sccm, the nitrogen flow rate is 8-15sccm, the sputtering power is 150-200W, and the bias working voltage is -50~-100V; the deposition time is 20min~30min, and the working pressure during sputtering is 0.34-0.4Pa; then ZrO is deposited under uninterrupted vacuum conditions. 2-XThe nitrogen gas was turned off, the argon gas flow rate was 15-30 sccm, the sputtering power was 150-200 W, the bias voltage was -50 V; the deposition time was 3h~4h30 min, and the working pressure during sputtering was 0.37-0.4 Pa; under the condition of uninterrupted vacuum, the ZrO 2-X A TiN layer is deposited on the surface of the layer, and argon and nitrogen are introduced into the vacuum chamber at the same time. During the deposition process, the argon flow rate is 15-30 sccm, the nitrogen flow rate is 8-15 sccm, the sputtering power is 180-250 W, and the bias working voltage is -50~-100 V; the deposition time is 20 min~30 min, and the working pressure during sputtering is 0.34-0.4 Pa; The above TiN / ZrO 2-X The / TiN composite coating is annealed at 700 ℃-800 ℃ in vacuum for 1-2 h, characterized in that the amorphous ZrO 2-X The coating is crystallized and oriented as monoclinic ZrO 2-X The phase ratio is greater than 94% and the grain size is uniform.

[0007] Deposition TiN / ZrO 2-X / TiN composite coating, in order to ensure the uniformity of the coating, the sample stage speed is 20 ~ 30 rpm; and the target substrate distance is 6 mm.

[0008] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts magnetron co-sputtering technology TiN / ZrO 2-X / TiN composite coating, annealed at 700 ℃-800 ℃ in vacuum for 1-2 h, characterized in that amorphous ZrO 2-X The coating is crystallized and oriented as monoclinic ZrO 2-X The phase ratio is greater than 94%, and the grain size is uniform. 2.5 The main component of the pre-film on the alloy surface is dense monoclinic zirconium oxide (ZrO 2-X ) and a small amount of tetragonal zirconia phase (ZrO 2 ) is equivalent, laying the foundation for subsequent hydrogen isotope injection and measurement; 2. TiN / ZrO of the present invention 2-X ZrO / TiN composite coating 2-X The standard deuterium isotope content in the layer is characterized by that ZrO 2-X The deuterium content in the coating is determined by setting the ion beam energy (5 KeV-50 KeV) parameters of the electrostatic ion accelerator or ion implanter to a predetermined ZrO 2-X The coating is injected or uniformly distributed with a certain amount of deuterium ions. This avoids the inhomogeneity of gas and electrolytic hydrogen isotopes in the oxide layer; 3. The present invention uses TiN to prevent the diffusion and escape of hydrogen isotopes, which has mature technology, low cost, strong process stability, and the prepared TiN has excellent effect in preventing hydrogen isotope escape, thereby improving the stability and reliability of hydrogen isotope standards; 4. TiN / ZrO of the present invention 2-X ZrO / TiN composite coating 2-X Deuterium isotope standard samples in the layer can be used to calibrate one-time spectrometry such as (inert gas fusion infrared absorption method), and can also be used to calibrate the results of multiple measurements of spectra and mass spectrometry (especially secondary ion mass spectrometry). TiN / ZrO 2-X ZrO / TiN composite coating 2-X The deuterium isotope standard sample in the layer has a stable structure and reliable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 for TiN / ZrO 2-X GIXRD diffraction pattern of the as-deposited coating.

[0010] Figure 2 for TiN / ZrO 2-X GIXRD diffraction pattern of the annealed coating.

[0011] Figure 3 for TiN / ZrO 2-X SEM image of the cross section of the annealed coating.

[0012] Figure 4 for TiN / ZrO 2-X AFM morphology image of the annealed surface of the coating.

[0013] Figure 5 for TiN / ZrO 2-X Photo of the standard sample after quantitative deuterium ion injection into the TiN coating. DETAILED DESCRIPTION

[0014] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but this does not mean any limitation on the protection content of the present invention.

[0015] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0016] A technology for preparing a standard sample of deuterium isotope content in a zirconium oxide layer, characterized in that the standard sample of deuterium isotope content in the zirconium oxide layer contains a specific phase structure ZrO 2-X(x<0.05) Contains a coating with a known isotopic deuterium content and a TiN deuterium diffusion barrier coating, TiN / ZrO 2-X / TiN is deposited on single crystal silicon (Si) or Zr-Nb 2.5The surface of the alloy substrate, wherein: the ZrO 2-X(x<0.05) In the coating, the value of x is <0.05; in the TiN deuterium diffusion barrier coating, the atomic ratio of Ti:N is close to an equiatomic ratio. 2-X In the layer, the value of x is <0.05, the monoclinic phase accounts for more than 90%, the grain size is evenly distributed, and the thickness is 550-600 nm. In a preferred embodiment, TiN / ZrO 2-X The / TiN composite coating is annealed at 700℃-800℃ in vacuum for 1-2 h, characterized in that the amorphous ZrO 2-X The coating is crystallized and oriented as monoclinic ZrO 2-X The phase ratio is greater than 94%, and the grain size is uniform. The present invention also provides a method for preparing a single crystal silicon (Si) or Zr-Nb 2.5 TiN / ZrO are deposited on the alloy substrate surface in sequence 2-X / The preparation method of TiN coating can adopt physical vapor deposition method or chemical vapor deposition method. In a preferred embodiment, any physical vapor deposition method such as magnetron sputtering and arc ion plating can be selected for coating deposition. In a more preferred embodiment, magnetron sputtering, especially ultra-high vacuum magnetron sputtering technology, is selected to prepare the coating. Compared with traditional surface treatment technology, magnetron sputtering has the advantages of low deposition temperature, good film quality, good uniformity, fast deposition speed, and can prepare large-area uniform and dense hard films. In a preferred embodiment, ZrO 2-X The deuterium content in the coating can be controlled by the ion beam energy (5 KeV-50 KeV) parameters of the electrostatic ion accelerator or ion implanter, at a predetermined ZrO 2-X The coating is obtained by injecting or uniformly distributing a certain number of deuterium ions into the coating. The specific implementation includes the following embodiments: Example 1

[0017] S0, according to the composition, ZrO is prepared by powder metallurgy technology 2-X and the target materials required for the TiN layer, respectively, to obtain ZrO 2 Target and Ti target; Using raw material powder with a purity higher than 99.9%, the target material with a diameter of 50.8 mm is prepared by powder metallurgy technology. The purity of the target material is higher than 99.9%. Among them, the purity of Ti target material reaches 99.95%; ZrO 2 The purity of the target material reaches 99.94%.

[0018] S1. The single crystal Si substrate was degreased and cleaned in an ultrasonic instrument using acetone and ethanol as solvents; then it was cleaned with deionized water and placed in a vacuum chamber of a magnetron sputtering instrument after drying. The vacuum system was used to make the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa; S2. Maintain the vacuum degree in the vacuum chamber <4.0×10 -4 Under the condition of 5 Pa, the single crystal Si substrate was back-sputtered and cleaned, the back-sputtering bias voltage was -700 V; the back-sputtering gas was argon; the back-sputtering pressure in the vacuum chamber was 5 Pa, and the back-sputtering cleaning lasted for 10 minutes; S3, keep the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa conditions, the target was cleaned by pre-sputtering for 15 min, where: the pre-sputtering power of the Ti target was 200 W; the pre-sputtering bias was -100 V; the pre-sputtering gas was argon; and the pre-sputtering pressure in the vacuum chamber was 0.38 Pa; S4, introducing argon and nitrogen into the vacuum chamber at the same time, first depositing a TiN layer on the single crystal Si substrate, during the deposition process, the argon flow rate is 20 sccm, the nitrogen flow rate is 8 sccm, the sputtering power is 200 W, and the bias working voltage is -100 V; the deposition time is 20 min, and the working pressure during sputtering is 0.38 Pa; S5, under uninterrupted vacuum conditions, ZrO is then deposited 2-X layer, nitrogen was turned off, the argon flow rate was 25 sccm, the sputtering power was 200 W, the bias operating voltage was -50 V; the deposition time was 4 h, and the working pressure during sputtering was 0.38 Pa; S6, under the condition of uninterrupted vacuum, then in ZrO 2-X A TiN layer is deposited on the surface of the layer, and argon and nitrogen are introduced into the vacuum chamber at the same time. During the deposition process, the argon flow rate is 20 sccm, the nitrogen flow rate is 8 sccm, the sputtering power is 200 W, and the bias working voltage is -100 V; the deposition time is 20 min min, and the working gas pressure during sputtering is 0.38 Pa; during the steps S4 to S6, the sample stage rotation speed is 20 to 30 rpm; the target substrate distance is 50 mm; S7, TiN / ZrO prepared by step S6 2-X The TiN / TiN composite coating was annealed at 700°C-800°C in vacuum for 0.5h; S8, using an electrostatic ion accelerator, the deuterium ion beam energy is 1.84 MeV, the beam current is 0.48 mA, and the deuterium ion beam flows through a 25 micron aluminum energy reduction sheet and then flows into a predetermined ZrO 2-X 5.68×10 15 Deuterium ions were obtained, and a standard sample of the deuterium isotope content (20 ppm) in the zirconium oxide layer was obtained.

[0019] The ZrO deposited on the surface of the single crystal Si prepared in step S5 is 2-XThe sample of ZrO / TiN double-layer coating is called 2-X / TiN deposited sample, ZrO 2-X The deposited TiN was placed in a tube furnace and annealed at 600-800°C for 30 min in an Ar protective atmosphere to obtain ZrO 2-X / TiN annealed sample. 2-X / TiN deposited samples, ZrO 2-X The structure of the annealed TiN / TiN samples was tested by X-ray diffraction (XRD). The test results are as follows: Figure 1 and Figure 2 As shown in the figure, the results show that the monoclinic ZrO with a ratio that meets the requirements can be obtained under 750℃ annealing conditions. 2-X The annealed ZrO 2-X The cross-sectional surface and morphology of the deposited TiN samples were characterized. Figure 3 and Figure 4 As shown. After step S8, TiN / ZrO 2-X / TiN coating injection 5.68×10 15 See the photo after deuterium ionization Figure 5 . Example 2

[0020] S0, according to the composition, ZrO is prepared by powder metallurgy technology 2-X and the target materials required for the TiN layer, respectively, to obtain ZrO 2 Target and Ti target; Using raw material powder with a purity higher than 99.9%, the target material with a diameter of 50.8 mm is prepared by powder metallurgy technology. The purity of the target material is higher than 99.9%. Among them, the purity of Ti target material reaches 99.95%; ZrO 2 The purity of the target material reaches 99.94%.

[0021] S1. For the single crystal Si substrate, the zirconium alloy substrate is ground and polished with water sandpaper of different roughness (80 mesh, 220 mesh, 400 mesh, 800 mesh, 1200 mesh, 2000 mesh) in turn. In this embodiment, the zirconium alloy is Zr-2.5Nb alloy. Then, acetone and ethanol are used as solvents to degrease and clean in an ultrasonic instrument; then, it is cleaned with deionized water, dried, and placed in the vacuum chamber of the magnetron sputtering instrument, and the vacuum degree in the vacuum chamber is made less than 4.0×10 -4 Pa; S2. Maintain the vacuum degree in the vacuum chamber <4.0×10 -4 Under the condition of 6 Pa, the zirconium alloy substrate was back-sputtered and cleaned, the back-sputtering bias voltage was -800 V, the back-sputtering gas was argon, the back-sputtering pressure in the vacuum chamber was 6 Pa, and the back-sputtering cleaning lasted for 15 minutes. S3, keep the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa conditions, the target was cleaned by pre-sputtering for 15 min, where: the pre-sputtering power of the Ti target was 200 W; the pre-sputtering bias was -100 V; the pre-sputtering gas was argon; and the pre-sputtering pressure in the vacuum chamber was 0.38 Pa; S4. Argon and nitrogen were introduced into the vacuum chamber at the same time, and a TiN layer was first deposited on the zirconium alloy substrate. During the deposition process, the argon flow rate was 20 sccm, the nitrogen flow rate was 8 sccm, the sputtering power was 200 W, and the bias working voltage was -100 V; the deposition time was 20 min, and the working pressure during sputtering was 0.38 Pa; S5, under uninterrupted vacuum conditions, ZrO is then deposited 2-X layer, nitrogen was turned off, the argon flow rate was 25 sccm, the sputtering power was 200 W, the bias operating voltage was -50 V; the deposition time was 4h30min, and the working pressure during sputtering was 0.38 Pa; S6, under the condition of uninterrupted vacuum, then in ZrO 2-X A TiN layer is deposited on the surface of the layer, and argon and nitrogen are introduced into the vacuum chamber at the same time. During the deposition process, the argon flow rate is 20 sccm, the nitrogen flow rate is 8 sccm, the sputtering power is 200 W, and the bias working voltage is -100 V; the deposition time is 20 min min, and the working gas pressure during sputtering is 0.38 Pa; during the steps S4 to S6, the sample stage rotation speed is 20 to 30 rpm; the target substrate distance is 50 mm; S7, TiN / ZrO prepared by step S6 2-X The TiN / TiN composite coating was annealed at 600°C-750°C in vacuum for 0.5h; S8, using an electrostatic ion accelerator, the deuterium ion beam energy is 1.81 MeV, the beam current is 0.47 mA, and the deuterium ion beam flows through a 25 micron aluminum energy reduction sheet and then flows into a predetermined ZrO 2-X 5.68×10 15 Deuterium ions were obtained, and a standard sample of the deuterium isotope content (20 ppm) in the zirconium oxide layer was obtained. Example 3

[0022] S0, according to the composition, ZrO is prepared by powder metallurgy technology 2-X and the target materials required for the TiN layer, respectively, to obtain ZrO 2 Target and Ti target; Using raw material powder with a purity higher than 99.9%, the target material with a diameter of 50.8 mm is prepared by powder metallurgy technology. The purity of the target material is higher than 99.9%. Among them, the purity of Ti target material reaches 99.95%; ZrO 2 The purity of the target material reaches 99.94%.

[0023] S1. The single crystal Si substrate was degreased and cleaned in an ultrasonic instrument using acetone and ethanol as solvents; then it was cleaned with deionized water and placed in a vacuum chamber of a magnetron sputtering instrument after drying. The vacuum system was used to make the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa; S2. Maintain the vacuum degree in the vacuum chamber <4.0×10 -4 Under the condition of 5 Pa, the single crystal Si substrate was back-sputtered and cleaned, the back-sputtering bias voltage was -700 V; the back-sputtering gas was argon; the back-sputtering pressure in the vacuum chamber was 5 Pa, and the back-sputtering cleaning lasted for 10 minutes; S3, keep the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa conditions, the target was cleaned by pre-sputtering for 15 min, where: the pre-sputtering power of the Ti target was 200 W; the pre-sputtering bias was -90 V; the pre-sputtering gas was argon; and the pre-sputtering pressure in the vacuum chamber was 0.38 Pa; S4, introducing argon and nitrogen into the vacuum chamber at the same time, first depositing a TiN layer on the single crystal Si substrate, during the deposition process, the argon flow rate is 20 sccm, the nitrogen flow rate is 8 sccm, the sputtering power is 200 W, and the bias working voltage is -100 V; the deposition time is 20 min, and the working pressure during sputtering is 0.38 Pa; S5, under uninterrupted vacuum conditions, ZrO is then deposited 2-X layer, nitrogen was turned off, the argon flow rate was 26 sccm, the sputtering power was 200 W, the bias operating voltage was -80 V; the deposition time was 5 h min, and the working pressure during sputtering was 0.38 Pa; S6, under the condition of uninterrupted vacuum, then in ZrO 2-X A TiN layer is deposited on the surface of the layer, and argon and nitrogen are introduced into the vacuum chamber at the same time. During the deposition process, the argon flow rate is 20 sccm, the nitrogen flow rate is 8 sccm, the sputtering power is 200 W, and the bias working voltage is -100 V; the deposition time is 20 min min, and the working gas pressure during sputtering is 0.38 Pa; during the steps S4 to S6, the sample stage rotation speed is 20 to 30 rpm; the target substrate distance is 50 mm; S7, TiN / ZrO prepared by step S6 2-XThe / TiN composite coating was annealed at 700 ℃-800 ℃ in vacuum for 40 min; S8, using an electrostatic ion accelerator, the deuterium ion beam energy is 1.81 MeV, the beam current is 0.45 mA, and the deuterium ion beam flows through a 25 micron aluminum energy reduction sheet and then flows into a predetermined ZrO 2-X 2.18×10 15 Deuterium ions were then generated, and the deuterium ion beam energy was changed to 1.78 MeV and the beam current was 0.46 mA. 2-X 3.5×10 15 Deuterium ions were used to obtain a standard sample of the deuterium isotope content (20 ppm) in the zirconium oxide layer.

Claims

1. A technology for preparing a standard sample of deuterium isotope content in a zirconium oxide layer, characterized in that: The deuterium isotope content standard sample in the zirconium oxide layer contains a specific phase structure ZrO 2-X(x<0.05) Contains a coating with a known isotopic deuterium content and a TiN deuterium diffusion barrier coating, TiN / ZrO 2-X / TiN is deposited on single crystal silicon (Si) or Zr-Nb 2.5 The surface of the alloy substrate, wherein: the ZrO 2-X(x<0.05) In the coating, the value of x is <0.05; in the TiN deuterium diffusion barrier coating, the atomic ratio of Ti:N is close to an equiatomic ratio.

2. The standard sample preparation technology for deuterium isotope content in zirconium oxide layer according to claim 1, characterized in that: The ZrO 2-X In the layer, the value of x is <0.05, the oriented monoclinic phase accounts for more than 90%, the grain size is evenly distributed, and the thickness is 550-600 nm; the Ti:N atomic ratio in the TiN coating is close to the equiatomic ratio, and the thickness is about 100-150 nm.

3. The standard sample preparation technology for deuterium isotope content in zirconium oxide layer according to claim 1, characterized in that: ZrO 2-X The deuterium content in the coating is determined by adjusting and designing the ion beam energy parameters of the electrostatic ion accelerator or ion implanter from 5 KeV to 50 KeV, and the ... the ion beam energy parameters of the electrostatic ion accelerator or 2-X The coating is obtained by implanting a certain number of deuterium ions in a normally distributed or uniformly distributed manner.

4. The preparation technology of standard sample of deuterium isotope content in zirconium oxide layer according to claims 1 to 2, characterized in that: Physical vapor deposition or chemical vapor deposition is used on single crystal silicon (Si) or Zr-Nb 2.5 TiN / ZrOx / TiN layers are deposited sequentially on the surface of the alloy substrate.

5. The method for preparing a standard sample of deuterium isotope content in a zirconium oxide layer according to claim 4, characterized in that: The physical vapor deposition method includes laser cladding, thermal spraying, cold spraying, magnetron sputtering, and arc ion plating.

6. The standard sample preparation technology for deuterium isotope content in zirconium oxide layer according to claim 5, characterized in that: The physical vapor deposition method is magnetron sputtering, wherein: ZrO 2-X During the deposition process of the coating: the argon flow rate is 15-30 sccm, the sputtering power is 180-250 W, and the bias working voltage is -50~-100 V; the deposition time is 3h~4h30 min, and the working pressure during sputtering is 0.37-0.4 Pa; during the deposition process of the TiN coating: the argon flow rate is 15-30 sccm, the nitrogen flow rate is 8-15 sccm, the sputtering power is 150-200 W, and the bias working voltage is -50~-100 V; the deposition time is 20 min~30 min, and the working pressure during sputtering is 0.34-0.4 Pa.

7. TiN / ZrO 2-X A method for preparing a TiN / TiN composite coating, characterized in that: The following steps are included: S0, according to the composition, ZrO is prepared by powder metallurgy technology 2-X and the target materials required for the TiN layer, respectively obtaining a ZrO2 target material and a Ti target material; S1, for single crystal Si substrate or Zr-Nb 2.5 The alloy substrate is ground and polished, then degreased and cleaned, and after drying, placed in the vacuum chamber of the magnetron sputtering instrument. The vacuum system is used to make the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa; S2. Maintain the vacuum degree in the vacuum chamber <4.0×10 -4 Under the condition of 2.5-6 Pa, the single crystal Si or zirconium alloy substrate is back-sputtered and cleaned, the back-sputtering bias voltage is -1000~-700V; the back-sputtering gas is argon; the back-sputtering pressure in the vacuum chamber is 2.5-6 Pa, and the back-sputtering cleaning takes 8-12 minutes; S3, keep the vacuum degree in the vacuum chamber less than 4.0×10 -4 Pa conditions, the target was cleaned by pre-sputtering for 15 minutes, wherein: the pre-sputtering power of the Ti target was 150-200W; the pre-sputtering bias was -50~-100 V; the pre-sputtering power of the Ti target was 150-200W; the pre-sputtering bias was -50~-100 V; the pre-sputtering gas was argon; the pre-sputtering gas pressure in the vacuum chamber was 0.37-0.4 Pa; S4. Argon and nitrogen are introduced into the vacuum chamber at the same time, and a TiN layer is first deposited on a single crystal Si or zirconium alloy substrate. During the deposition process, the argon flow rate is 15-30 sccm, the nitrogen flow rate is 8-15 sccm, the sputtering power is 150-200 W, and the bias working voltage is -50~-100 V; the deposition time is 20 min~30 min, and the working pressure during sputtering is 0.34-0.4 Pa; S5, under uninterrupted vacuum conditions, ZrO is then deposited 2-X layer, turn off nitrogen, argon flow rate is 15-30 sccm, sputtering power is 150-200 W, bias working voltage is -50 V; deposition time is 3h~4h30 min, working pressure during sputtering is 0.37-0.4 Pa; S6, under the condition of uninterrupted vacuum, then in ZrO 2-X A TiN layer is deposited on the surface of the layer, and argon and nitrogen are introduced into the vacuum chamber at the same time. During the deposition process, the argon flow rate is 15-30 sccm, the nitrogen flow rate is 8-15 sccm, the sputtering power is 180-250 W, and the bias working voltage is -50~-100 V; the deposition time is 20 min~30 min, and the working gas pressure during sputtering is 0.34-0.4 Pa; during the steps S4~S6, the sample stage rotation speed is 20~30 rpm; the target substrate distance is 50 mm.

8. TiN / ZrO according to claim 7 2-X A method for preparing a TiN / TiN composite coating, characterized in that: In the steps S4 and S6, the argon flow rate is 25 sccm, the nitrogen flow rate is 9 sccm, the sputtering power is 150W, the bias working voltage is -50V, the deposition time is 20 min, and the working gas pressure during sputtering is 0.38Pa; in the step S5, the argon flow rate is 25 sccm, the sputtering power is 200W, the bias working voltage is -50V; the deposition time is 4.0 h, and the working gas pressure during sputtering is 0.38Pa.

9. TiN / ZrO according to claim 7 2-X A method for preparing a TiN / TiN composite coating, characterized in that: Vacuum high temperature 700 ℃-800 ℃ annealing for 1-2 h, amorphous ZrO 2-X The coating is crystallized and oriented as monoclinic ZrO 2-X The phase ratio is greater than 94% and the grain size is uniform.

Citation Information

Patent Citations

  • Zirconium cladding surface resistant to high temperature and oxidation ZrCrFe / AlCrFeTiZr composite gradient coating preparing technology

    CN107513694A

  • Method for detecting deuterium content distribution in tungsten by using radio frequency glow discharge spectrometer

    CN110531403A

  • Method for detecting hydrogen diffusion inhibition performance of titanium nitride film

    CN116183444A

  • Hydrogenating of member made of zirconium-base alloy

    JP1999335807A

  • A method for hydrogen ion implanting into Zirconium alloy using proton beam

    KR1020100069256A